Toxic Masculinitites under the Microscope of Social Psychology Theory - Supratiwi (Buana Gender: Jurnal Studi Gender dan Anak, 2024)
Reporting on sexual violence, domestic violence, and various other abusive behaviors has become one of the concrete outcomes caused by the existence of "Toxic Masculinity". It is no longer unfamiliar that the prevailing social norms still dictate how men should behave. The social construct in creating a norm sometimes gives rise to situations that seem biased and oppressive for individuals who are compelled to adhere to and live by it for social acceptance. This research discusses how toxic masculinity is present, cultivated, and perpetuated in everyday life, examining it from the perspective of Social Psychology theory. The type of approach used in this research is qualitative-descriptive, explaining the phenomena that occur in the community. Primary data sources consist of five informants from Gorontalo, while secondary sources come from references such as books and journals. The research technique involves the use of interviews, and the analysis of results is conducted using content analysis. The findings of this research reveal that the formation of toxic masculinity can be observed through the process of social identity, social perception, and social influence on an individual. Keywords: Toxic Masculinity, Social Psychology